UNODA Occasional Papers No. 33 - United Nations (United Nations, 2019)
This publication provides a historic overview of the efforts within the United Nations to reduce military spending. It examines how the discussions on reducing military budgets have evolved in disarmament forums over the last decades. This includes early efforts to pursue the reduction of military spending throughout the Cold War period as a distinct objective of general and complete disarmament, the emergence of efforts related to promoting transparency on military matters, and the various workstreams carried out under the banner of the relationship between disarmament and development.